2018
DOI: 10.18433/jpps29770
|View full text |Cite
|
Sign up to set email alerts
|

Licofelone Attenuates LPS-induced Depressive-like Behavior in Mice: A Possible Role for Nitric Oxide

Abstract: -PURPOSE: Licofelone, a dual cyclooxygenase/5-lipoxygenase inhibitor, possesses antioxidant, antiapoptotic, neuroprotective, and anti-inflammatory properties. The aim of the present study was to investigate the effect of licofelone on lipopolysaccharide (LPS)-induced depression in a mouse model and also a possible role for NO. METHODS: To elucidate role of NO on this effect of licofelone (5 and 20 mg/kg, i.p.), L-NAME, a nonspecific NO synthase (NOS) inhibitor; aminoguanidine (AG), a specific inducible NOS (iN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In preclinical studies, the cytokine inducer LPS has been demonstrated to promote behavioral alterations in mice, some of which, resemble depressive symptoms in humans [33]. Using two validated depression tests in rodents, the FST and the TST, we observed that LPS administration increased immobility time indicating an increase in depressive-like behavior, which is in agreement with previous studies [34,35]. Apart from the classical depressive symptoms, evidence indicates that depressed patients also display cognitive impairment [36].…”
Section: Discussionsupporting
confidence: 90%
“…In preclinical studies, the cytokine inducer LPS has been demonstrated to promote behavioral alterations in mice, some of which, resemble depressive symptoms in humans [33]. Using two validated depression tests in rodents, the FST and the TST, we observed that LPS administration increased immobility time indicating an increase in depressive-like behavior, which is in agreement with previous studies [34,35]. Apart from the classical depressive symptoms, evidence indicates that depressed patients also display cognitive impairment [36].…”
Section: Discussionsupporting
confidence: 90%
“…LPS treatment causes expression of certain depression‐like symptoms in rodents (Yirmiya, 1996) and is clinically relevant to human depression (Alvarez‐Mon et al., 2019). Administration of LPS is frequently used to study neuroinflammation‐associated diseases in mice (Zhao et al., 2019); ergo this model enables a focus on the inflammatory‐related pathways in depression (Dantzer et al., 2008; Mousavi et al., 2019; Remus & Dantzer, 2016; Walker et al., 2019). Systemic LPS can trigger a pro‐inflammatory response and microbicidal responses through engagement of pattern recognition receptors such as Toll‐like receptors on immune cells (Amarante‐Mendes et al., 2018).…”
Section: A Role For Inflammation‐driven Leakiness Of Barriersmentioning
confidence: 99%
“…15 Furthermore, licofelone has been shown to exert antidepressant-like effects probably through its anti-inflammatory property. 16 In line with this, other COX inhibitors, either selective (nimesulide, rofecoxib and celecoxib) or non-selective (aspirin, naproxen), have been examined in animal seizure models, suggesting an elevation in the seizure threshold. 45 In the present study, the effects of acute administration of five different doses of licofelone (1, 3, 5, 10, and 20 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, licofelone can exert antidepressant-like ef-fects probably due to its anti-inflammatory properties. 16 Collectively, these studies point toward an instrumental therapeutic role of dual COX/5-LOX inhibitors in CNS disorders in which oxidative stress plays a key role. Consistent with this notion, the protective effect of licofelone in epileptic disorders has been investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%